Echoes of the Second Vatican Council in «Estudios Eclesiásticos» - Molina, S.J., Diego M. (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
This article presents the way in which the review Estudios Eclesiásticos announced the celebration and development of the Second Vatican Council (1962-1965). For this purpose, the author has picked up a series of articles that were published in the magazine on the occasion of the ecumenical council. In those studies have been analyzed the most significant documents: Lumen gentium, Dei Verbum, Sacrosanctum Concilium.